2021
DOI: 10.1111/apce.12327
|View full text |Cite
|
Sign up to set email alerts
|

Decentralization and welfare: Evidence from a panel of countries

Abstract: This study empirically tested for the relationship between different measures of decentralization and three indicators of welfare-per capita income, poverty incidence, and the human development index. It utilized a panel data of around 60 countries of various income levels for the ten-year period from 2006 to 2015. The study primarily employed the System GMM method, along with some robustness checks. Results suggest that decentralization is associated with higher per capita income; but it has no relationship w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 77 publications
1
6
0
Order By: Relevance
“…Furthermore, the balancing fund has a significant effect on GRDP per capita of 0.821727, so every 1% increase will increase by 0.821727%. These results are in line with previous studies conducted by Canare, (2021) and Hao et al (2020), where that regional revenues from central government transfers have a positive effect on per capita income. This shows that the balancing fund has the potential to increase welfare in general.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…Furthermore, the balancing fund has a significant effect on GRDP per capita of 0.821727, so every 1% increase will increase by 0.821727%. These results are in line with previous studies conducted by Canare, (2021) and Hao et al (2020), where that regional revenues from central government transfers have a positive effect on per capita income. This shows that the balancing fund has the potential to increase welfare in general.…”
Section: Resultssupporting
confidence: 93%
“…Based on the regression results table, the previous year's original regional income variable (lnpad -1) has a significant effect on per capita GRDP, an increase in the previous year's Local Revenue by 1% will increase per capita GRDP by 0.173394%. his result is supported by research conducted by Canare (2021) who found that fiscal autonomy can have a positive effect on increasing per capita income.…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…In general, as can be appreciated in the cited surveys, the evidence on the effects of decentralizing are mixed in the case of economic growth, positive on governance, and also positive in health and especially education outcomes. Surprisingly, although the objective of many decentralization initiatives is to improve economic welfare and human development, there is a lack of empirical literature on the effects of decentralization on variables reflecting human welfare, such as poverty, per capita PPP income, and the human development index, Canare (2021b) being a notable exception. Also, the majority of cross‐country contributions focusing on education and health outcomes have used subnational government spending or revenue as a percentage of total spending or revenue to account for decentralization, and just a few employed more disaggregated decentralization indicators reflecting the decentralization of spending in these specific policy areas.…”
Section: Introductionmentioning
confidence: 99%
“…The liberal approach emphasizes decentralization for better organizational efficiency in providing goods and services, for environmentally sustainable development, and in promoting local development through citizen participation. The researchers' interest in the consequences of decentralization for the economy focused mainly on economic growth, and some studies indicate that there is an optimal level of decentralization that maximizes the growth rate of the economy (Martinez-Vasquez et al, 2017;Camões, 2022;Canare, 2022).…”
Section: Introductionmentioning
confidence: 99%